Simple synthesis of the novel antihistaminic drug olopatadine hydrochloride - Chavan, Subhash P.; Lasonkar, Pradeep B. (Synthesis-Stuttgart, 2013)
A new alternative route for the synthesis of olopatadine is described. The present strategy involves a Lewis acid mediated ring opening of a cyclic ether to introduce 3-(dimethylamino)propylidene group as the side chain.
Keywords: antihistaminic drugs; chelates; Lewis acids; spiro compounds; zinc